A Chicken Farm and Chilli Plants in Cingkes Village for Agricultural Development and Economic - Annisa Ilmi Faried; Rahmad Sembiring; Uswatun Hasanah (Budapest International Research and Critics University, 2022)
Once of the flagship programs of North Sumatra Province is strengthening the role of the agricultural sector by utilizing the potential for integration through simple innovations that can convert livestock manure into organic fertilizer, thereby increasing the nutrition of agricultural land and utilizing agricultural waste as animal feed. It tries to build an integrated system that functions to increase and maintain income while taking into account the welfare of farmers and farmers. An increase in household income and an increase in agricultural and plantation yields can be resulted from the development relationship between these two variables. With the aim of improving the financial welfare of farmers' and ranchers' households by creating an ideal business model for integrating chicken with food crops.